Competencias Digitales y Desempeño Docente del Área de Matemáticas - Cabezas Rojas, Lourdes Susana (2023)
ABSTRACT: The research work analyzed the influence of digital competencies on the teaching performance in the area of Mathematics in the 6th year of basic education at the "Juan de Velasco" Educational Unit. The beneficiaries were 37 students in the 6th year of GBS at the "Juan de Velasco" Educational Unit and 4 teachers of Mathematics who teach at the same level, The instruments that were applied were a survey to the students with 10 questions that allowed to know the performance of teachers with digital competences and a survey to the teachers that allowed to know their performance with digital competences before and after the pandemic. The research determines that teachers with digital competencies before the pandemic was relatively good, however, during the development of virtual classes in times of health emergency, teachers have improved their digital competencies, this product of the permanent interaction with technological tools, acquiring new skills.